What 736 Plastic Surgeons Think about Explantation and Capsulectomy: A Global Opinion Poll. Issue 6 (29th March 2022) - Scheflan, Michael; Gronovich, Yoav; Maisel Lotan, Adi; Winder, Gilad
Abstract : Background: Breast implant illness, although not classified as a disease entity, has recently gained significant attention globally. The purpose of this study was to assess the status of explantation practices, discuss plastic surgeon's attitude toward requests for explantation and capsulectomy, and evaluate surgical management when accepting these challenges. Methods: Twenty closed-ended multiple choice questions were formulated to an opinion poll. The anonymous opinion poll was distributed to members of American Society for Aesthetic Plastic Surgery and presidents of plastic surgery societies on all continents. Results: A total of 736 plastic surgeons responded to the opinion poll. Although geographic variation was noted, a majority of 69.8 percent stated that explantation surgery had increased in their practice compared to the previous year. Requests for explantation without capsulectomy met with high acceptance rates among surgeons, regardless of whether patients were asymptomatic or not. Patients who also requested capsulectomy received less enthusiastic replies depending on the type of practice, years in practice, implant position, and type of capsulectomy (en bloc, total, or partial). When fat grafting was indicated, 68.7 percent stated that simultaneous lipofilling is limited when capsulectomy is performed, yet 44.5 percent stated that they would remove thin normal capsules in a symptomatic patient even when simultaneous fat grafting is requested by the patient. Conclusion: The opinion poll supports the hypothesis that demand for explantation and capsulectomy increased globally among symptomatic and asymptomatic patients; that attitudes toward simultaneous capsulectomy are divided; and that management may differ according to geographic location, experience, and type of practice.